Forced vibration testing of footbridges using calibrated human shaker and wireless sensors. (2017) - Brownjohn, James; Bocian, Mateusz; Hester, David
Abstract: Wireless inertial measurement units (IMUs) designed for biomechanical applications have been evaluated for modal testing of civil structures, in particular footbridges, where the small size and high response levels match the sensor capabilities. Building on research into recovery of ground reaction forces (GRFs) in walking and jumping directly using a treadmill or force plate, it has been found that a single carefully located IMU can successfully recover GRFs in open space conditions on full-scale structures. Amplitudes of first and second harmonics of the GRFs can be recovered with consistent and small bias errors by multiplying resolved vertical component acceleration by body mass. Of the many potential applications, one with immediate use is the ability to carry out forced vibration tests without mechanical excitation. All that is needed is to record the acceleration of a structure along with that of a human jumping so as to generate a strong harmonic component at the structure's natural frequency. There are caveats involving identification of mode shape and satisfying requirements of the relevant system identification procedure, but the procedure has been applied successfully to two very different footbridges. The procedure and the results for these two bridges are described in the paper.